To determine which segment on triangle DEF is congruent to segment BC from triangle ABC, we need to first identify the coordinates of the points in both triangles.
For triangle ABC:
- Point A is at \( (3, 2) \)
- Point B is at \( (3, 6) \)
- Point C is at \( (6, 2) \)
Now, let's find the length of segment BC:
- The coordinates of points B and C are \( (3, 6) \) and \( (6, 2) \), respectively.
- The length of segment BC can be calculated using the distance formula: \[ BC = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \] Substituting the coordinates of B and C: \[ BC = \sqrt{(6 - 3)^2 + (2 - 6)^2} = \sqrt{(3)^2 + (-4)^2} = \sqrt{9 + 16} = \sqrt{25} = 5 \]
Now, we look at triangle DEF, which is the reflection of triangle ABC across the y-axis:
- Point D is at \( (-3, 2) \)
- Point E is at \( (-3, 6) \)
- Point F is at \( (-6, 2) \)
Now, we check the segments of triangle DEF:
- Segment DE: \[ \text{Length of DE} = \sqrt{(-3 - (-3))^2 + (6 - 2)^2} = \sqrt{0^2 + 4^2} = \sqrt{16} = 4 \]
- Segment EF: \[ \text{Length of EF} = \sqrt{(-6 - (-3))^2 + (2 - 6)^2} = \sqrt{(-3)^2 + (-4)^2} = \sqrt{9 + 16} = \sqrt{25} = 5 \]
- Segment FD: \[ \text{Length of FD} = \sqrt{(-3 - (-6))^2 + (2 - 2)^2} = \sqrt{(3)^2 + 0^2} = \sqrt{9} = 3 \]
After checking the lengths of the segments in triangle DEF, we find segment EF has a length of 5, which is congruent to segment BC.
Therefore, the answer is: segment EF.